2015
DOI: 10.1021/acschembio.5b00214
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Ultrastructural Localization Underlie the Pro-apoptotic Activity of a Hydrocarbon-stapled BIM BH3 Peptide

Abstract: Hydrocarbon stapling has been applied to restore and stabilize the α-helical structure of bioactive peptides for biochemical, structural, cellular, and in vivo studies. The peptide sequence, in addition to the composition and location of the installed staple, can dramatically influence the properties of stapled peptides. As a result, constructs that appear similar can have distinct functions and utilities. Here, we perform a side-by-side comparison of stapled peptides modeled after the pro-apoptotic BIM BH3 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 35 publications
5
43
0
2
Order By: Relevance
“…We first confirmed that BIM SAHB A1 and BIM SAHB A -3 have equivalent cellular uptake, as quantified by ImageXpress Micro (IXM) high content epifluorescence microscopy of treated A375P cells and mouse embryonic fibroblasts (MEFs), which we have used previously to benchmark the comparative cell penetrance of FITC-labeled stapled peptides(Bird et al, 2016) (Figure S3A–B). The mechanism of uptake for BIM SAHBs is consistent with macropinocytosis, as previously reported(Edwards et al, 2015; Walensky et al, 2004) and evidenced here by the epifluorescence microscopy pattern of treated A375P and MEF cells at 4 hours (Figure S3C–D). …”
Section: Resultssupporting
confidence: 90%
“…We first confirmed that BIM SAHB A1 and BIM SAHB A -3 have equivalent cellular uptake, as quantified by ImageXpress Micro (IXM) high content epifluorescence microscopy of treated A375P cells and mouse embryonic fibroblasts (MEFs), which we have used previously to benchmark the comparative cell penetrance of FITC-labeled stapled peptides(Bird et al, 2016) (Figure S3A–B). The mechanism of uptake for BIM SAHBs is consistent with macropinocytosis, as previously reported(Edwards et al, 2015; Walensky et al, 2004) and evidenced here by the epifluorescence microscopy pattern of treated A375P and MEF cells at 4 hours (Figure S3C–D). …”
Section: Resultssupporting
confidence: 90%
“…Overall, CAPA data supported that ZF5.3, BIM-SAHB A1 , and DP1 can access the cytosol more effectively than Tat, as suggested by previous literature. 2830 …”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of the p53/human double minute 2 (Hdm2) interaction is of particular interest in this context, and a variety of studies on different variants of stapled peptides have been published (Walensky et al, 2004;Chang et al, 2013). Remarkably, despite their size, these stapled peptides have been shown to enter cells and reach their targets in the cytosol (Muppidi et al, 2014;Chu et al, 2015;Edwards et al, 2015). These properties have been linked to the constrained helical character of the peptides (Kim and Verdine, 2009).…”
Section: Introductionmentioning
confidence: 99%